2018
DOI: 10.1002/ca.23196
|View full text |Cite
|
Sign up to set email alerts
|

Defining the width of the normal tibial plateau relative to the distal femur: Critical normative data for identifying pathologic widening in tibial plateau fractures

Abstract: Tibial plateau widening in the setting of fracture is an indication for surgical treatment, and restoring width is an important goal of surgery. In order to identify and correct pathological widening, the width of the normal tibial plateau must first be defined. The aim of this study was to establish normative data for the width of the tibial plateau relative to the distal femur to enable surgeons to identify and correct pathological widening in the setting of tibial plateau fracture. Fifty-one uninjured anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 13 publications
3
27
0
5
Order By: Relevance
“…This study aligns well with the previous work of Johannsen et al, who showed that the tibial plateau is slightly wider than the distal femur. 7 This study met our goal of trying to identify a width ratio across ages and genders. We found that the width ratio is always at or slightly greater than 1.0 with advanced age and between genders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aligns well with the previous work of Johannsen et al, who showed that the tibial plateau is slightly wider than the distal femur. 7 This study met our goal of trying to identify a width ratio across ages and genders. We found that the width ratio is always at or slightly greater than 1.0 with advanced age and between genders.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent similar study investigating the width ratio demonstrated that AP radiographs were reliable and there was little variation compared with using CT scans. 7 Furthermore, using ratios instead of individual widths eliminates magnification and calibration concerns. The results of our study would have been strengthened if a second researcher would have made all measurements and those measurements were compared with that of the author whose measurements were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The tibial articular width is slightly wider than the femoral articular width (tibia:femur articular width ratio was found to be 1.01 ± 0.04 in one study of healthy knees) [13]. With this in mind it might be useful to use the femur as a reference to judge pathologic tibial plateau widening and adequacy of intraoperative reductions [13,14]. The lateral plateau is more proximal and slightly convex whereas the medial plateau is more concave and slightly distal to the lateral plateau.…”
Section: Anatomymentioning
confidence: 99%
“…However, Wang et al [87] were unable to predict soft tissue injury based on tibial plateau widening. Johannsen et al [14] suggest that discrepancies in the literature on condylar widening can be reconciled by instead using a ratio of the articular widths of the femur and tibia in order to minimize problems in measurement with magnification and calibration.…”
Section: Surgical Indicationsmentioning
confidence: 99%
“…We expected the automated grid to correspond to manual measurements for direction (AP and ML) and angulation (medial proximal tibial angle [MPTA] and tibial slope in the sagittal plane). 1,10,15,25 We also expected the actual postoperative tibial tunnel aperture position to be within proximity of the ideal tunnel location, described in the literature at 40% in the AP axis and 51% in the ML axis from the medial origin. 6,9,20…”
mentioning
confidence: 98%